O câncer de mama em mulheres envelhescentes e idosas - Ferraz, Lúcia Teixeira Lopes (2006)
The early detection and prevention of breast cancer in middle age and elderly age women, through the analysis of their bodily symptoms, is the main purpose of this article. The world is undergoing a transformation both in its demography and in its epidemiology. Demographically, the aging of our population is a direct consequence of the increase of the life expectancy. Thought observed in both sexes, this increase is greater for women. Epidemiologically, these changes in demographics have caused a change in the cause of death profile of the population. One of the representations of these changes is the fall in the death-rate of infect-contagious diseases, characteristic of younger populations, and a rise in the death-rate of chronicle diseases, which are characteristic of populations with a predominance of older people. In Brazil, cancer is one of the main causes of death among the elderly, being breast cancer one of the main female causes of death. The public health policy is geared mainly towards the early detection of this disease, being the clinical mammography and ultra-sound exams the main methods used. However, these diseases are usually diagnosed too late, frequently leading to deaths. For the purposes of this research, a qualitative approach was adopted. The chosen subjects were middle age and elderly women who were frequent patients at Jardim Colorado s basic health unit, in Suzano, São Paulo. The chosen procedure was an interview with each subject in separate. The main focus of the interview was to get to know which signs these women looked for in their bodies and which procedures they adopted to diagnosis breast cancer on themselves. Through this series of interviews, it was discovered that the mere transmission of information regarding the prevention of breast cancer is not enough to ensure that the recommended procedures are followed. This implies that health campaigns by themselves are not as effective if not accompanied by procedures that ensure both that these women incorporate and use the knowledge acquired as well as that they routinely visit health units in order to undergo the necessary exams. It was thus concluded that, in the specific subject of early cancer detection in middle age and elderly women, it s mandatory that public policies focus in creating in younger women a culture in which it s common for people to frequently visit public health systems to be examined